2018
DOI: 10.1002/cre2.114
|View full text |Cite
|
Sign up to set email alerts
|

Study of factors related to the attitudes toward studying abroad among preclinical/clinical undergraduate dental students at three dental schools in Japan

Abstract: Despite of their general interests in studying abroad, there are two types of dental student in Japan. They are those who decide to go studying abroad and those who do not. The aim of this study was to clarify the factors related to the attitudes toward studying abroad among preclinical/clinical undergraduate dental students who attended three dental schools in Japan. A questionnaire was used to assess undergraduate dental students' attitudes toward studying abroad. We analyzed the differences between junior (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…For example, medical students who achieved higher scores in "openness to experiences" were more likely to underperform academically, 19 delay their graduation, 20 have a higher incidence of non-suicidal self-injury, 21 have higher patient empathy scores, 22 and be inducted into the Gold Humanism Honor Society (a compassionate patient care society), 23 while Japanese dental students were more likely to study abroad. 24 Pharmacy students with higher levels of "agreeableness" were found to have lower levels of depression 25 and to take longer to complete examinations, 26 while medical students demonstrated an interest in homeopathy and acupuncture elective courses and in rural medical specialties. 27,28 Finally, neuroticism was higher in medical students than in surgical trainees, 29 higher in dental students in Southeast Asia, 30 and lower among medical school graduates than medical students who left the program.…”
Section: Resultsmentioning
confidence: 99%
“…For example, medical students who achieved higher scores in "openness to experiences" were more likely to underperform academically, 19 delay their graduation, 20 have a higher incidence of non-suicidal self-injury, 21 have higher patient empathy scores, 22 and be inducted into the Gold Humanism Honor Society (a compassionate patient care society), 23 while Japanese dental students were more likely to study abroad. 24 Pharmacy students with higher levels of "agreeableness" were found to have lower levels of depression 25 and to take longer to complete examinations, 26 while medical students demonstrated an interest in homeopathy and acupuncture elective courses and in rural medical specialties. 27,28 Finally, neuroticism was higher in medical students than in surgical trainees, 29 higher in dental students in Southeast Asia, 30 and lower among medical school graduates than medical students who left the program.…”
Section: Resultsmentioning
confidence: 99%
“…Dental students with experience of studying abroad or plans to study overseas scored higher in "openness to experience. 19 " In the present survey, we did not include any questions to examine the personality of participants. However, the dental students who spent their school life with international students indicated an "acceptance of different cultures" and "awareness of the need for intercultural competence in the dental profession.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the present study showed that dental graduates (dental trainees) who were exposed to the international learning environment tend to have more international experiences outside of the classroom. Dental students with experience of studying abroad or plans to study overseas scored higher in “openness to experience 19 …”
Section: Discussionmentioning
confidence: 99%
“…Student outbound mobility in dental education is reported (25), but to a lesser extent compared with other health professions (30)-only 16 articles were found. Furthermore, validation and outcomes research on goals is still limited (55,56,65,69). However, if IoDE is to be implemented to a larger extent, research on outcomes of such programs is needed, and standardized formats need to be agreed upon.…”
Section: Student Exchangesmentioning
confidence: 99%
“…Therefore, countries and schools aim to provide their graduates with English language skills in order to share scientific knowledge and to remain competitive in the world ranking. Although not explicitly stated as a motivation, articles that described the theoretical benefits of language programs were coded as motivation for the market model-creating a global workforce and/or enhancing competition (41,55,61,62,70,71,79). Of note, two articles found in this category were published in non-English journals with an English abstract (41,70).…”
Section: Motivations For Iodementioning
confidence: 99%